Routledge companion to critical and cultural theory - Simon Malpas; Wake Paul (London Routledge, 2024)
Theory, history, context; structuralism and semiotics; narrative and narratology; Marxism; poststructuralism;historicism;psychoanalytic criticism;deconstruction;feminism;gender and queer thoery;postmodernism;race and postcoloniality; green thory;trauma studies.
Keywords: Literary theory and criticism